PENYELESAIAN SENGKETA PERBANKAN SYARIAH DI INDONESIA - Dewi Utami Sari (Al-Munqidz : Jurnal Kajian Keislaman, 2020)
The development of financial institutions and syaria banking is so fast, but in terms of legal regulations it still lags. Among the regulations that still need to be improved is the regulation of resolute dispute syaria banking. Where in this case there is still a juridical problem there is dualism of judicial authority in the resolute dispute syaria banking. The results showed that the dispute resolution of syaria banking in Indonesia can be done through two ways, both litigation and non-litigation.Religion Court has the authority to resolve syaria banking disputes on litigation ways, while the non-litigation can be done through deliberation, banking mediation. National Sharia Arbitration Board is the most strategic forum for resolving disputes about banking Sharia outside the court because it could resolve the dispute quickly, simply and at low cost.